A decade of environmental change in the Pacific Arctic region. (August 2015) - Wood, Kevin R.; Bond, Nicholas A.; Danielson, Seth L.; Overland, James E.; Salo, Sigrid A.; Stabeno, Phyllis J.; Whitefield, Jonathan
Highlights: Loss of multiyear sea ice resulted in an open-water dominated environment in summer. Fluctuations in large-scale atmospheric circulation also affected the ecosystem. Wider extremes of variability a hallmark of the 'new normal' in the Pacific Arctic. Abstract: Over the decade 2004–2013 environmental changes in the Pacific sector of the Arctic have been dramatic enough to suggest that a 'new normal' climate is emerging. The clearest indicator of this change is the dramatic loss of sea ice during the summer, which in some years has already resulted in essentially ice-free conditions in this region. For example, between 7 August and 11 October 2012, sea ice concentration in the Beaufort and Chukchi Seas between 70 and 80°N fell below 20% (with a record minimum concentration of only 5% on 2 September). Thick multiyear sea ice (older than 2 years) has almost entirely disappeared, replaced by thin and more mobile first-year ice. Year-to-year variability in ice concentration is associated with anomalous wind forcing linked to larger-scale atmospheric circulation patterns, which also affect ocean currents, including transport through Bering Strait. With reduced sea ice extent the area of ice-free ocean susceptible to rapid solar heating has increased. More heat is stored in the upper ocean early in the summer melt season and persists later into the autumn freeze-up. Monthly surface air temperature anomalies greater than 6 °C have occurred frequently in the autumn in the Beaufort and Chukchi seas. Environmental variations in the Bering Sea over the last decade have been subtle by comparison, and include an increase in winter sea-ice extent between 2007 and 2013.